Transformasi Pendidikan Usia Dini: Strategi Pemasaran Digital untuk Meningkatkan Citra Sekolah dan Profesionalisme Guru PAUD - Sudarso, Satrio; Kusuma Wardana, Mahardika Darmawan; Redani Zaenha, Mochamad Abdi; Masfufah, Hanem; Yulianti, Mila (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – Community service activities at TK ABA Purwosari showed the importance of using digital tools and training teachers to optimise technology and create interactive content in early childhood education. The collaborative effort between the community service team of Universitas Muhammadiyah Sidoarjo and PCA Purwosari shows digital marketing training is needed to improve school reputation and teachers‘ digital skills which in accordance with this objective includes improving teachers’ digital capabilities and the application of digital marketing strategies to improve educational outcomes and school reputation. Methodology –. This mentoring and training is to equip educators with skills in educational technology and digital promotion strategies so that they can improve student learning outcomes and raise awareness about school enterprises. The program includes direct instruction, observation, interviews, stakeholder coordination, evaluation through focus groups and questionnaires. Findings – The program significantly improved teachers' skills in creating engaging promotional content and learning materials. Training provided includes using Canva for presentations, CapCut for videos, Instagram for promotions, and Google My Business for visibility. Tools such as Kahoot and Math Playground enhance interactive learning, while paper crafts boost creativity. High teacher satisfaction and positive feedback indicate the success of the program. Originality – The service program at TK ABA 1 Purwosari and TK ABA 2 Al Wathan improved educational practices and marketing strategies through constructivist-based training and related support activities.